Changes in distribution of indigenous forest in Table Mountain National Park from 1880-2012 - Poulsen, Zoe Chapman (Department of Biological Sciences, 2014)
South Africa's indigenous forest only covers 0.56% of the country's total land area. Its highly fragmented distribution and historically extensive exploitation has led it to be perceived as one of the South Africa's most vulnerable vegetation types. Despite this, forest remains one of South Africa's most under-researched ecosystems and the country has few dedicated forest ecologists. This research examines changes in distribution of Western Cape Afrotemperate Forest and Western Cape Milkwood Forest in Table Mountain National Park. Forest – Fynbos spatial ecotonal change and forest patch count was mapped from 1944 to 2008 using aerial photographs in ArcGIS 10. A full survey of species composition was undertaken and this dataset was used to produce an objective classification of the Cape Peninsula forests. Ground-based repeat photography was used to determine land cover change from 1880 to present with finer scale resolution. An analysis using transition matrices projects future land cover changes to 2050. A total of 174 forest patches were identified in Table Mountain National Park. Total indigenous forest cover has increased by 65.3% from 1944 to 2008. This increase was predominantly visible within the Peninsula's Western Cape Afrotemperate Forest and the highest expansion rates were recorded in Orange Kloof and Blinkwater Ravine on Table Mountain. Only 13 of the forest patches surveyed decreased in cover after 1944. Most of these patches were areas of Western Cape Milkwood Forest located in proximity to expanding coastal development. This trend was also reflected in the repeat photography dataset. There has also been an increase in vegetation biomass recorded at all sites. Further research is required to determine whether these changes have caused a decrease in fynbos species diversity. Non-parametric statistical analysis showed no correlation of forest change with variation in aspect, temperature, precipitation, geology, soils or fire frequency post 1975. These findings indicate that forest patches are influenced by localised ecological factors and suggests a dominant role for other drivers. Historical evidence indicates the key driver of forest expansion is vegetation recovery from past high fire frequency alongside the influence of current fire suppression policies. Increases in CO2 may also be a contributory factor although localised variation in extent of forest expansion suggests that this is not the strongest driver of change. These results hold significance for the future ecological management of Table Mountain National Park in the face of changing climate.